2006
DOI: 10.1677/joe.1.06553
|View full text |Cite
|
Sign up to set email alerts
|

A GH receptor antisense oligonucleotide inhibits hepatic GH receptor expression, IGF-I production and body weight gain in normal mice

Abstract: Diabetic retinopathy and acromegaly are diseases associated with excess action of GH and its effector IGF-I, and there is a need for improved therapies. We have designed an optimised 2 -O-(2-methoxyethyl)-modified phosphorothioate oligodeoxynucleotide, ATL 227446, and demonstrated its ability to suppress GH receptor mRNA in vitro. Subcutaneous injections of ATL 227446 reduced GH receptor mRNA levels, GH binding activity and serum IGF-I levels in mice after seven days of dosing.The reduction in serum IGF-I coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Theoretically, this could be accomplished by the construction of GH receptor antagonists and by RNA antisense techniques, thus preventing the synthesis of the GH receptor. Indeed, the recently developed antisense oligonucleotide, ATL 227446, effectively inhibited hepatic GH receptor expression and IGF-I production and decreased body weight gain in mice (Tachas et al 2006). Below we shall review the molecular structure of GH and its receptor and physiology which all are keystones for the development of GH receptor antagonists.…”
Section: Gh Antagonistsmentioning
confidence: 99%
“…Theoretically, this could be accomplished by the construction of GH receptor antagonists and by RNA antisense techniques, thus preventing the synthesis of the GH receptor. Indeed, the recently developed antisense oligonucleotide, ATL 227446, effectively inhibited hepatic GH receptor expression and IGF-I production and decreased body weight gain in mice (Tachas et al 2006). Below we shall review the molecular structure of GH and its receptor and physiology which all are keystones for the development of GH receptor antagonists.…”
Section: Gh Antagonistsmentioning
confidence: 99%
“…Studies in experimental animals have shown promising results in the control of diabetic nephropathy and a variety of cancers, and clinical studies in this area are certainly warranted [11]. We have recently reported that an alternative to pegvisomant, modified antisense oligonucleotides to the GHR, is able to lower serum IGF-1 in mice to similar levels as pegvisomant, and inhibits long-term body weight gain in mice [31]. These remain to be clinically tested.…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of IGF-I was observed over 10 weeks of dosing. In cynomolgus monkeys, ATL-1103 given twice weekly over a period of 6 weeks suppressed IGF-I levels by 35% in comparison to placebo [178]. In a Phase I clinical trial with 36 healthy adult male subjects, the drug showed a significant decrease of IGF-I as well as a significant reduction in GH-binding protein (GHBP) by 16% after 3 weeks (press release, Antisense Therapeutics).…”
Section: Antisense Drugs 731 Atl-1103mentioning
confidence: 99%